The Republic of Beliefs : A New Approach to ‘Law and Economics’ - Basu, Kaushik (World Bank, Washington, DC, 2015)
The discipline of law and economics deals with wide-ranging topics, from competition and environmental policy to crime control, and has been instrumental in determining how an economy performs. Yet its success has fallen short of its potential. The discipline’s shortcomings are nowhere as visible as in developing economies, where a common refrain is how the law looks good on paper but does not get implemented. This paper articulates a methodological flaw that underlies much of contemporary law and economics, and argues that there is an intimate connection between human beliefs and expectations, on the one hand, and the effectiveness of the law, on the other. I propose a new approach to law and economics that is rooted in game theory and rectifies the flaw. It is argued that this approach can open up new areas of research and be marshalled to address some of the more pressing policy challenges of our time.